A cautionary tale on the use of GE‐7031 varnish: low‐temperature thermal expansion studies of ScF3. (15th May 2013) - Morelock, Cody R.; Suchomel, Matthew R.; Wilkinson, Angus P.
Abstract : GE‐7031 varnish, a commonly used low‐temperature adhesive and electrical insulator owing to its high thermal conductivity and mechanical strength at low temperatures, was used as a sample matrix for low‐temperature powder X‐ray diffraction measurements of the negative thermal expansion (NTE) material ScF3 . When ScF3 powder was mixed with GE‐7031 varnish, an unexpected cubic to rhombohedral phase transition in the ScF3 sample was observed at ∼50 K, and it exhibited smaller low‐temperature unit‐cell volumes than samples without the varnish matrix. Experimental observations and quantitative estimates suggest that these anomalies are the result of stress induced by a thermal expansion mismatch between the varnish matrix (large positive coefficient of thermal expansion, CTE) and ScF3 (quite large negative CTE). The use of GE‐7031 varnish as a sample matrix for low‐temperature measurements should be approached with caution if a large thermal expansion mismatch is expected.